Characterization of Cu3SbS3 thin films grown by thermally diffusing Cu2S and Sb2S3 layers - Hussain, A. (Elsevier B.V., 2017)
Copper antimony sulfide (Cu3SbS3) with a p-type conductivity and optical band gaps in the range of 1.38 to 1.84 eV is considered to be a promising solar harvesting material with non-toxic and economical elements. In this study, we reported the fabrication of Cu3SbS3 thin films using successive thermal evaporation of Cu2S and Sb2S3 layers followed by annealing in an argon atmosphere at a temperature range of 300–375 °C. The structural and optical properties of the as-deposited and annealed films were investigated. The annealed films notably show the crystalline phase of Cu3SbS3, identified from the X-ray diffraction analysis and endorsed by the Raman analysis as well, whereas the chemical state of the constituent elements was characterized using X-ray photoelectron spectroscopy. The measured highest resistivity of the annealed film was found to be ~ 0.2 Ω-cm. Hence, our obtained results for the fabricated Cu3SbS3 thin films bring to light that these films would be good as absorber layer in solar cells due to their low resistivity, higher optical absorption coefficient (~ 105 cm− 1), low transmittance (< 5%) and an optical direct band gap of 1.6 eV in the visible range of the solar spectrum.